Hepatic metastases of colorectal cancer are rather homogeneous but differ from primary lesions in terms of immune cell infiltration - Halama, Niels; Berthel, Anna; Lerchl, Tina; Brand, Karsten; Herpel, Esther; Welte, Stefan Ezechiel; Keim, Sophia; Lahrmann, Bernd; Klupp, Fee; Kahlert, Christoph; Weitz, Jürgen; Grabe, Niels; et al. (OncoImmunology, 2013)
The immune system plays an important role in shaping the clinical course of colorectal cancer (CRC). However, it is still unclear how the immune infiltrates of primary CRC lesions and distant metastases by immune effector cells are related to each other. To address this issue, we quantified CD3+, CD8+ and granzyme B+ lymphocytes in primary CRC samples and corresponding liver metastases. This analysis showed that the prognostic predictions that can be drawn from the infiltration of immune cells in primary CRCs and their metastases are heterogeneous. To investigate whether such heterogeneity would also be observed within CRC hepatic metastases, the density of the immune infiltrate and cytokine production were assessed in opposite sides of the same metastatic lesion. In addition, tumor-infiltrating lymphocytes were assessed in sequential sections of the same metastatic lesion, with a spacing of 30 μm. In summary, consistent cell counts and cytokine levels were detected within the same lesion. The study of a case of synchronous metastases, however, suggested that different metastatic lesions within the same patient may be heterogeneous, perhaps indicating a major impact for local causes on tumor infiltration by immune cells. In summary, our study demonstrates a consistent degree of heterogeneity between primary tumors and hepatic metastases but an excellent intra-lesional homogeneity. These findings may be of key importance for patient stratification and the development of personalized strategies against CRC.
Gesehen am 13.10.2021